ENGLISH LANGUAGE TEACHING METHODOLOGY - Javliyeva Firuza (Bright Mind Publishing, 2025)
This article analyzes the methodology of teaching English, its modern approaches and methods for increasing its effectiveness. The role of new pedagogical technologies, interactive methods, communicative approach and information technologies in the process of teaching English is considered. Also, international experiences in teaching foreign languages and their application in the education system of Uzbekistan are considered.
Keywords: English methodology, communicative approach, interactive education, linguodidactics, modern technologies, language competence, teaching foreign languages.